Determinants of livelihood strategies of fishing households in the volta Basin, Ghana - F. K. Y. Amevenku; R. K. Asravor; John K. M. Kuwornu (Cogent Economics & Finance, 2019)
The main objective of this study is to identify livelihood strategies of fishing households in response to prevalent vulnerabilities they face within the Volta Basin. Questionnaires were administered to fishery households in the Basin using the multistage sampling technique. A non-hierarchical k-means cluster analysis partitioned the households into four livelihood strategies on which the multinomial logit regression was performed. These four identified strategies are fishery only, fishery and farming, fishery and non-farm, and fishery, non-farming and farming. The results from the multinomial logit regression revealed that marital status of head of household, number of months of food shortage experienced by a household per year, access to credit, access to extension services, distance to regular markets and district capital as well as experience in fishery were the major determinants of livelihood strategies. Implications for policy include the need for public extension services and training to invigorate fishery households' income. As majority of the fishery households combined fishing and non-fishing strategies, livelihood intervention programmes should prioritize improvement of the non-fishing activities and lead to opening other opportunities for rural development. This will take pressure off the fish stock by facilitating the regeneration of fish stock.
Keywords: 330; volta Basin; cluster analysis; k-means; livelihood strategy; diversification